Implementation of the Vroom-Yetton Model in Mitigating Teacher’s Interpersonal Conflict: An Analysis of Workload Distribution Policy in Schools - Wiwiyanti Wiwiyanti; Amrina Rosyada; Reni Listiowati; Ngurah Ayu Nyoman Murniati (Journal of Educational Sciences, 2026)
The management of teacher workload and decision-making processes in schools plays a crucial role in shaping organizational climate and teacher well-being. This study analyzes the implementation of the Vroom–Yetton Decision Model in managing teacher workload distribution as an effort to mitigate interpersonal conflict at SD Negeri Wangkelang. A qualitative case study approach was employed involving the principal and teachers as key informants. The findings indicate that teacher workload distribution is not yet fully proportional, particularly in non-teaching assignments, leading to perceptions of unfairness among teachers. This condition contributes to work stress, reduced job satisfaction, and latent interpersonal conflicts within the school environment. Although these conflicts are not openly expressed, they still affect collaboration and working relationships among teachers. Furthermore, the decision-making process in workload allocation remains dominated by the principal, with limited teacher participation. This shows that the Vroom–Yetton Model has not been optimally implemented in a participative manner. The lack of involvement reduces teachers’ sense of ownership toward school policies and increases organizational tension. The study integrates workload distribution, participatory decision-making, and interpersonal conflict within the Vroom–Yetton framework, offering insights for more participative leadership to improve fairness, job satisfaction, and school climate.